(untitled) (Research, Society and Development, 2022)
The present study aimed to evaluate the menus of Brazilian university restaurants, regarding the offer of vegetarian dishes, diversity of preparations and qualitative aspects. A survey of menus from 68 Brazilian public universities was carried out, including 43. Presence and variety of vegetarian preparations, number of salads and meat-based preparations were analyzed, in addition to qualitative aspects through the qualitative evaluation method of menu preparations. The average number of days of menus analyzed was 24.02±4.34, among Brazilian regions, with the majority (95.35%) offering vegetarian preparations, with an average weekly frequency of 5.22±1.44 days , regardless of region. The options of salads and meats were 2.21±0.99 and 1.37±0.61, respectively. Significant differences were found between the regions for the qualitative components: leafy (p=0.02), equal colors (p=0.04) and foods rich in sulfur (p=0.001). The classification of the nutritional and sensory quality of the menus was good for the positive aspects (fruits and leafy vegetables), ranged from fair to excellent in the negative aspects (sweets, fried foods and sweets associated with fried foods), and presented as regular and poor in the components monotony of colors and foods rich in sulfur. In view of the above, it was noted that the evaluated restaurants offered, for the most part, a vegetarian option daily, at least two salad options and one meat option. Although some qualitative aspects differ between regions, most of the menus were adequate for the recommended components.